2022
DOI: 10.1021/acsomega.2c01757
|View full text |Cite
|
Sign up to set email alerts
|

Study on Mechanical Properties and Crack Propagation of Raw Coal with Different Bedding Angles based on CT Scanning

Abstract: The deformation and damage characteristics of coal are the important foundation that affects the fracturing potential of coal reservoirs and the development plan of coalbed methane (CBM). To reveal the influence regulation of primary fractures and the bedding angle of coal on its failure and provide theoretical basis for CBM development, raw coal samples of no 16 coal seam in Wenjiaba Coal Mine, Zhijin County, Bijie City with different bedding angles were selected as the research object, and uniaxial compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Guizhou is one of the largest coal resource provinces in southern China and one of China's coal resource and coalbed methane enrichment areas. The mining area of Guizhou Province is representative 28 , 29 . The study area is located in the east wing of Qianxi Mountain, which is roughly extended by more than 50 km in the direction of 40° northeast.…”
Section: Geological Survey Of Mining Areamentioning
confidence: 99%
“…Guizhou is one of the largest coal resource provinces in southern China and one of China's coal resource and coalbed methane enrichment areas. The mining area of Guizhou Province is representative 28 , 29 . The study area is located in the east wing of Qianxi Mountain, which is roughly extended by more than 50 km in the direction of 40° northeast.…”
Section: Geological Survey Of Mining Areamentioning
confidence: 99%
“…Influence of bedding on the fracture pattern of the coal mass during blasting was investigated Zhao et al [21]. Yuan et al [22] revealed the influence of primary fractures and the bed angle of the coal on its deformation and damage characteristics. Huang et al [23,24] used the double-exposure holographic interference method to observe the evolution of strain field of barite before destruction.…”
Section: Introductionmentioning
confidence: 99%